Results of the Marine Ice Sheet Model Intercomparison Project, MISMIP - Pattyn, Frank; Schoof, Christian; Perichon, Laura; Hindmarsh, Richard; Bueler, Ed.; De Fleurian, B; Durand, Gil; Gagliardini, Olivier; Gladstone, R; Goldberg, D.; Gudmundsson, G.H; Lee, V; et al. (2012)
info:eu-repo/semantics/published